2016
DOI: 10.1103/physrevlett.117.085501
|View full text |Cite|
|
Sign up to set email alerts
|

New Ground-State Crystal Structure of Elemental Boron

Abstract: Elemental boron exhibits many polymorphs in nature based mostly on an icosahedral shell motif, involving stabilization of 13 strong multicenter intraicosahedral bonds. It is commonly accepted that the most thermodynamic stable structure of elemental boron at atmospheric pressure is the β rhombohedral boron (β-B). Surprisingly, using high-resolution transmission electron microscopy, we found that pure boron powder contains grains of two different types, the previously identified β-B containing a number of rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…An et al Reply: Our Letter reported high-resolution transmission electron microscopy on commercial quality boron showing that ∼2=3 of the grains exhibit smooth microstructure, leading to an x-ray diffraction pattern of well-known beta boron [1]. The other 1=3 grains exhibit a uniform zigzag pattern that extends across the entire grain and exhibits a very regular twinlike symmetry on every other lattice plane.…”
mentioning
confidence: 89%
“…An et al Reply: Our Letter reported high-resolution transmission electron microscopy on commercial quality boron showing that ∼2=3 of the grains exhibit smooth microstructure, leading to an x-ray diffraction pattern of well-known beta boron [1]. The other 1=3 grains exhibit a uniform zigzag pattern that extends across the entire grain and exhibits a very regular twinlike symmetry on every other lattice plane.…”
mentioning
confidence: 89%
“…Well-established α, β, γ , and tetragonal T allotropes are superhard, and have been confirmed to be pure boron allotropes [1]. Recently, yet another pure bulk modification of boron, τ -B [2], and two-dimensional (2D) allotropes of boron, borophenes, were identified [3,4]. Boron oxide B 2 O 3 and suboxide B 6 O are well established, but there are also controversial compounds proposed in the literature [4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Among the most fundamental is determining the thermodynamically stable ground state between two competing forms: α-rhombohedral boron, which contains B 12 icosahedra exclusively [4], and β-rhombohedral boron (β-B in the following), which exhibits partial occupations and geometric frustration, most unusual for an elemental ground-state structure [5][6][7][8][9]. The energy difference between the α and β forms has been studied extensively using density-functional theory (DFT) [8][9][10][11][12][13][14][15] and recently probed by calorimetric experiments [16]; the consensus is now that β-B is indeed more stable at ambient conditions.…”
mentioning
confidence: 99%